SERUM VITAMIN E, C AND A LEVEL IN LUNG CANCER: A CASE CONTROL STUDY - Md. Ramatullah; M. Rafique; , Aktaruzzaman; Md. Nazrul Islam Khan; Sheikh Nazrul Islam (European Scientific Journal, ESJ, 2013)
Lung cancer is a leading cause of cancer death worldwide, causing approximately 1.2 million deaths per year. Lung cancer is prevalent in smokers. It is documented that smoking induces oxidative stress, which is thought to be associated with the aetiology of carcinogenesis. A case control cross sectional study was conducted on sixty lung cancer patients and sixty smokers as cohort control. Serum levels of antioxidant vitamin E, C and A among the case and control subjects were estimated. It was observed that vitamin E value among the study population did not alter (15.67±3.67μmol/L vs. 14.66±3.88μmol/L). It was within normal range. Conversely, there was significantly high serum concentrations of vitamin C and A in the lung cancer patients as compared to those in the smoker controls (48.26±6.81versus 16.65±4.46μmol/L; 2.76±0.32 versus 1.60±0.35μmol/L respectively).